Fenomena Perempuan sebagai Subjek Kekerasan Berbasis Gender - Lyna Novianti; Endah Kusumawati; Khilmatushofa Khilmatushofa (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
Gender equality and justice has placed women in thoughts, behaviors, and decisions that are no longer limited by the patriarchal system. However, in the midst of women’s efforts to build justice, instead of fighting for and upholding the role of women, the phenomenon of disputes and interactions between women themselves is increasingly striking and so prevalent on social media and the reality of life in modern Indonesia. This unbalanced relationship then has an impact as happened in Gender-Based Violence (KBG). No doubt, this action is the same as reinforcing injustice to women. Therefore, this study aims to determine the forms of injustice perpetrated by the same sex, especially women against women based on the five social experiences of women and KBG. This study uses descriptive-qualitative methods and data collection techniques through questionnaires and literature study. Data obtained from the results of questionnaires filled out by 54 respondents taken by purposive sampling technique. While the data analysis techniques in this study are data collection, data reduction, data presentation and verification. The results of the study indicate that violence against women has the potential to be carried out by fellow women. In addition, the forms of violence that are often experienced by women from female KBG perpetrators are psychological violence, in the form of: body shaming, talkative in the form of belittling and demeaning in terms of education, work, and married life. Meanwhile, in terms of five social experiences, women are more likely to receive stigmatization, subordination and marginalization.